A Fall from (Someone Else’s) Certainty: Recovering Practical Wisdom in Teacher Education - Phelan, Anne (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
Inquiry‐based teacher education promotes an exploration of concrete particulars as the route to wise practice. The case study presented illustrates one teacher candidate’s struggle to let go of a conception of knowledge as generalizable formulae that can be readily applied in practice and to become more open to practice itself as a site of learning. Teacher educators can nurture such openness by helping aspiring teachers to appreciate the fragility of knowledge, the epistemological value of feeling, and the priority of the particular, in teaching. In so doing, educators recover practical wisdom as the beginning and end‐in‐view of teacher education. Key words: practical wisdom, preservice teacher education, inquiry La formation à l’enseignement axée sur la recherche favorise la prise en compte des conditions particulières et, de ce fait, une pratique éclairée. L’étude de cas présentée dans cet article illustre les efforts d’une candidate à l’enseignement en vue de se départir d’une conception de la connaissance définie comme une formule généralisable, facilement applicable dans la pratique, et de mieux accueillir la pratique elle‐même comme un lieu d’apprentissage. Les responsables de la formation à l’enseignement peuvent contribuer à cette ouverture en aidant les futurs enseignants à saisir la fragilité de la connaissance, la valeur épistémologique des sentiments et l’importance des conditions particulières dans l’enseignement. Ce faisant, les éducateurs redécouvrent la sagesse comme le début et l’objectif à atteindre dans la formation à l’enseignement. Mots clés : sagesse pratique, formation à l’enseignement, recherche.